2021
DOI: 10.20396/zet.v29i00.8660951
|View full text |Cite
|
Sign up to set email alerts
|

Sentido numérico em crianças

Abstract: O presente estudo examinou, em uma perspectiva de desenvolvimento, três indicadores de sentido numérico: significado dos números, magnitude relativa dos dígitos em números e distância entre números na sequência numérica. Cinquenta crianças alunas do 1º e 2º ano do Ensino Fundamental realizaram três tarefas, cada uma relativa a um desses indicadores. Utilizou-se a Análise de Agrupamentos para definir o perfil dos participantes quanto ao conhecimento que apresentavam sobre números que foram divididos em dois gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The findings reveal that the general performance of children in making sense of the number magnitude is at a high level. In this study, children showed the highest performance in the second type of questions about number comparison, in line with the research findings of Spinillo, Correa, and Cruz (2021). These are questions that require comparison of numbers symbolically and as a numerosity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings reveal that the general performance of children in making sense of the number magnitude is at a high level. In this study, children showed the highest performance in the second type of questions about number comparison, in line with the research findings of Spinillo, Correa, and Cruz (2021). These are questions that require comparison of numbers symbolically and as a numerosity.…”
Section: Discussionsupporting
confidence: 90%
“…Within the scope of the study, interview questions were developed by taking into account the number sense components defined in the literature (Jordan, Glutting, & Ramineni, 2010, Spinillo, 2018Spinillo, Correa, & Cruz, 2021;Friso-van den Bos, Kroesbergen, & Van Luit, 2014).…”
Section: Data Collection Toolmentioning
confidence: 99%